Pharmacological interventions for agitated behaviours in patients with traumatic brain injury: a systematic review. Issue 7 (9th July 2019) - Williamson, David; Frenette, Anne Julie; Burry, Lisa D; Perreault, Marc; Charbonney, Emmanuel; Lamontagne, Francois; Potvin, Marie-Julie; Giguère, Jean-Francois; Mehta, Sangeeta; Bernard, Francis
Abstract : Objective: The aim of this systematic review was to assess the efficacy and safety of pharmacological agents in the management of agitated behaviours following traumatic brain injury (TBI). Methods: We performed a search strategy in PubMed, OvidMEDLINE, Embase, CINAHL, PsycINFO, Cochrane Library, Google Scholar, Directory of Open Access Journals, LILACS, Web of Science and Prospero (up to 10 December 2018) for published and unpublished evidence on the risks and benefits of 9 prespecified medications classes used to control agitated behaviours following TBI. We included all randomised controlled trials, quasi-experimental and observational studies examining the effects of medications administered to control agitated behaviours in TBI patients. Included studies were classified into three mutually exclusive categories: (1) agitated behaviour was the presenting symptom; (2) agitated behaviour was not the presenting symptom, but was measured as an outcome variable; and (3) safety of pharmacological interventions administered to control agitated behaviours was measured. Results: Among the 181 articles assessed for eligibility, 21 studies were included. Of the studies suggesting possible benefits, propranolol reduced maximum intensities of agitation per week and physical restraint use, methylphenidate improved anger measures following 6 weeks of treatment, valproic acid reduced weekly agitated behaviour scale ratings and olanzapine reduced irritability, aggressiveness and insomnia between weeks 1 and 3 of treatment. Amantadine showed variable effects and may increase the risk of agitation in the critically ill. In three studies evaluating safety outcomes, antipsychotics were associated with an increased duration of post-traumatic amnesia (PTA) in unadjusted analyses. Small sample sizes, heterogeneity and an unclear risk of bias were limits. Conclusions: Propranolol, methylphenidate, valproic acid and olanzapine may offer some benefit; however, they need to be further studied. Antipsychotics may increase the length of PTA. More studies on tailored interventions and continuous evaluation of safety and efficacy throughout acute, rehabilitation and outpatient settings are needed. PROSPERO registration number: CRD42016033140